(untitled) (Andamios, Revista de Investigación Social, 2024)
This article presents an analysis of the discursive construction of conservation around two biosphere reserves, which is a global category established to name spaces with ecosystem characteristics of interest for conservation. Regarding the theoretical-methodological proposal, multimodal discourse analysis tools are used that allow the integration of various forms of discursive production and dissemination. Finally, the conservation discourses around the Mayan Biosphere Reserves (Petén, Guatemala) and Montes Azules (Chiapas, Mexico) are compared by identifying the contrasts (similarities and differences) between the ways of understanding environmental conservation expressed by the social actors linked to said spaces.